As concepções sobre o processo de leitura e escrita de uma professora alfabetizadora do meio rural - Ávila, Cinthia Cardona de (2012)
This paper presents the results obtained from research developed in Programa de Pós- Graduação em Educação of Universidade Federal de Santa Maria - PPGE/UFSM, linked to Line of research 1 - Training, Knowledge and Professional Development. Through this research, it was possible to realizethe ideas that guide the practice of a literacy teacher active in a rural school in Santa Maria/RS. For the writing of this work wasnecessary to use references that could buttress information gathered during the research in the fields of Life History, Literacy, History of Education, Educational Practice. To this end, stood out: Minayo (2010), Gatti; André (2010), Macedo (2006), Souza (2006), Antunes (2004, 2005, 2011, 2011a), Freire (1977, 1996), Freire; Macedo (2011), Soares (2010). The methodology that bases this research was a qualitative approach, using the Life History. For the collection ofinformation were used to report Autobiographical Writing, Meetings Approach, Semi- Structured Interview, Journaling Field. The conceptions of literacy have been built throughout his teaching career, the group work undertaken by rural teachers in multigrade classes that experience in the participant of this research appeared in his early career. Thus, it was throughout their experienceswithin the school and the countryside that the teacher has designed the current design that we have today about the process ofreading and writing. Throughout the meetings occurred during the period of data collection, there was a noticeable involvement andengagement of the teacher with the school and the rural areas, spaces that are part of their personal and professional life for 27 years. With that,during the research, it was noted the practice of liberation, emotional, loving, guiding the theory base of educator Paulo Freire (1996).